The Extradition Bill of Hong Kong revisited, the National Security Law and the irony of human rights protection in “one country, two systems” - Miguel Lemos; Miguel João Costa (Revista Brasileira de Direito Processual Penal)
This article focuses on two recent episodes that shook the Hong Kong Special Administrative Region of the People’s Republic of China. It analyzes the main features of the failed Extradition Bill and confronts them with those of the National Security Law that was later enacted by the People’s Republic of China. It also addresses the question as to whether the latter’s provisions are in breach of the basic policies for Hong Kong agreed upon in 1984 between the United Kingdom and the PRC. It concludes that, rather ironically, while the failed Extradition Bill was largely in tune with those basic policies and the human rights protections enshrined therein, the National Security Law is not.